Navigating the perils and pitfalls throughout the consent process in hematopoietic cell transplantation. (May 2023) - Cusatis, Rachel; Litovich, Carlos; Spellecy, Ryan; Liang, Andrew; D'Souza, Anita
Abstract: Hematopoietic cell transplantation (HCT) is a complex treatment used in malignancies and some non-malignant diseases. The informed consent process for HCT can also be complex due to patient- and process-related barriers. The informed consent process needs to be a dynamic and ongoing process, not simply a checklist. As a result of the realities of HCT, we highlight some potential pitfalls to the informed consent process including uncertainty, sociocultural and communication barriers, and decisional regret. The purpose of this comprehensive review is to highlight unique situations which can result in failure of the informed consent process. We also offer potential solutions to these pitfalls, primarily making the informed consent more patient focused through dynamic and continuous processes to mitigate decisional regret.